2021
DOI: 10.3389/fmed.2021.732054
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-Led Education for Final Year Medical Students: A Pilot Study

Abstract: Background: Prescribing is a core skillset for medical officers. Prescribing errors or deficiencies can lead to patient harm and increased healthcare costs. There is an undefined role for pharmacist-led education to final year medical students to improve prescribing skills.Aim: Assess if pharmacist-led education on prescription writing improves the quality and safety of final year medical students' prescribing skills.Method: Participants and Intervention: Final year medical students were randomised into tutori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Most of the included studies showed positive results for improved prescribing skills of medical student’s post-educational interventions. 11 studies reported statistically significant improvements in prescription writing outcomes of the intervention group or from pre to post-test [ 3 , 6 , 10 , 12 , 25 , 26 , 29–33 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the included studies showed positive results for improved prescribing skills of medical student’s post-educational interventions. 11 studies reported statistically significant improvements in prescription writing outcomes of the intervention group or from pre to post-test [ 3 , 6 , 10 , 12 , 25 , 26 , 29–33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies implemented mixed-method teaching [ 6 , 10 , 25 , 28 , 31 , 33 ]. Three studies combined clinical placement with educational interventions [ 10 , 25 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations